Modeling the process of musical creativity in musical instrument digital interface format - Sergey V. Chibirev, Irina B. Gorbunova, (Opción, 2019)
This article considers applying mathematical modeling to write music scores in the MIDI (Musical Instrument Digital Interface) format. The scores are viewed as an abstract text created by analyzing statistical parameters with the subsequent modeling of musical creativity as per the obtained data. As a result, the developed method can be used to analyze other types of difficult-to-formalize abstract texts in various subject areas—for example, when studying biological and social processes. In conclusion, the developed approach can be used to analyze other types of abstract difficult-to-formalize texts in various subject areas: for example, when studying biological and social processes.